A battery positive electrode material and preparation method thereof, positive electrode sheet, and lithium ion battery
By using heteroatom doping carbon materials in the coating layer of the phosphate-based positive electrode material, the problem of low conductivity is solved, the rate performance is improved, and it is suitable for high-power batteries.
Patent Information
- Application Number
- CN202311279134.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-27
AI Technical Summary
Due to the low conductivity of the phosphate positive electrode material, its rate performance in lithium-ion batteries is low, limiting its application in the field of high-power batteries.
By using heteroatom doping carbon material in the cladding layer of the phosphate-based active material, the conductivity of the carbon material is improved. The heteroatom is selected from Group IIIA elements, and the doping amount is controlled from 1% to 5% by weight to enhance the conductivity of the positive electrode material.
The conductivity of the positive electrode material is improved, thereby improving its rate performance in lithium-ion batteries, and is suitable for applications of high-power batteries.
Smart Images

Figure CN117276507B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion battery technology, and specifically to a battery positive electrode material and a preparation method thereof, a positive electrode sheet, and a lithium-ion battery. Background Art
[0002] Phosphate-based positive electrode materials have an olivine structure and have the advantages of abundant raw materials, low cost, and high mass-to-capacity ratio. They are currently one of the main positive electrode materials for power lithium-ion batteries.
[0003] Phosphate-based cathode materials include lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate. Polyanionic cathode materials, represented by lithium iron phosphate, offer excellent performance, are environmentally friendly, and are safe, making them highly promising cathode materials for lithium-ion batteries. However, the low electrical conductivity of phosphate-based cathode materials results in poor rate performance and other characteristics in lithium-ion batteries, limiting their application in high-power batteries. Summary of the Invention
[0004] In response to the problems existing in the prior art, the embodiments of the present application provide a battery positive electrode material and its preparation method, a positive electrode plate, and a lithium-ion battery, aiming to improve the electrical conductivity of the positive electrode material and thereby improve its rate performance when applied to lithium-ion batteries.
[0005] In a first aspect, an embodiment of the present application provides a battery positive electrode material, comprising a phosphate-based active material core and a coating layer coating the phosphate-based active material core, wherein the coating layer comprises a heteroatom-doped carbon material, wherein the heteroatom comprises at least one of Group IIIA elements, and the heteroatom content in the heteroatom-doped carbon material is 1 wt% to 5 wt%.
[0006] The battery positive electrode material provided in the embodiment of the present application uses heteroatoms to dope carbon materials to obtain heteroatom-doped carbon materials, which are used as coating layers for phosphate-based active materials. The heteroatoms are selected from group IIIA elements, and the valence of group IIIA elements forming ions is mainly +3. When they are used to dope carbon, the band structure of the carbon material is changed, thereby improving the conductivity of the carbon coating layer. During the doping process, the heteroatoms replace the positions of the carbon atoms and form covalent bonds with the carbon atoms, and generate hole carriers in the carbon material lattice, increasing the concentration of hole carriers in the carbon material, thereby improving the conductivity of the carbon material. When such heteroatom-doped carbon materials are used as coating layer materials for phosphate-based active materials, the conductivity of the positive electrode material can be further improved, thereby improving its rate performance when applied to secondary batteries.
[0007] In some embodiments of the present application, the heteroatom includes one or more combinations of B, Al, and Ga.
[0008] In some embodiments of the present application, the thickness of the coating layer is 2 to 5 nm.
[0009] In some embodiments of the present application, the mass ratio of graphitized carbon to amorphous carbon in the heteroatom-doped carbon material is (0.6-2):1.
[0010] In some embodiments of the present application, the active material core comprises a chemical formula of Li x M y N z An active material for PO4, wherein M is selected from at least one element of Fe, Mn, Co, and Ni, N is selected from at least one element of V, Al, Ti, Ni, Nb, Mg, and Zr, 0.9≤x≤1.1, 0.9≤y≤1, and 0.001≤z≤0.08.
[0011] In some embodiments of the present application, the carbon content of the positive electrode material is 0.5 wt % to 2 wt %.
[0012] In some embodiments of the present application, the average particle size Dv50 of the positive electrode material is 0.5 to 1.5 μm.
[0013] In some embodiments of the present application, the specific surface area of the positive electrode material is 8 to 30 m 2 / g.
[0014] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material for a battery, comprising:
[0015] providing phosphate-based active materials and heteroatom-doped carbon materials respectively;
[0016] mixing the heteroatom-doped carbon material and the phosphate-based active material and subjecting them to ball milling to obtain a positive electrode material precursor;
[0017] The positive electrode material precursor is sintered in an inert atmosphere to obtain a battery positive electrode material.
[0018] In some embodiments of the present application, the mass percentage of the heteroatom-doped carbon material relative to the phosphate-based active material is 0.5% to 2%.
[0019] In some embodiments of the present application, providing the heteroatom-doped carbon material includes: taking a carbon source and a heteroatom source and performing a calcination treatment to obtain the heteroatom-doped carbon material.
[0020] In some embodiments of the present application, the heteroatom source includes one or more compounds containing Group IIIA elements.
[0021] In some embodiments of the present application, the carbon source includes one or more combinations of glucose, sucrose, and starch.
[0022] In some embodiments of the present application, the mass percentage of the heteroatom source relative to the carbon source is 1% to 5%.
[0023] In some embodiments of the present application, providing the phosphate-based active material includes: reacting a lithium source, a phosphorus source, an M source, and a N source, and separating a solid after the reaction to obtain the phosphate-based active material.
[0024] In some embodiments of the present application, the N source includes one or more combinations of vanadium-containing compounds, aluminum-containing compounds, titanium-containing compounds, nickel-containing compounds, niobium-containing compounds, magnesium-containing compounds, and zirconium-containing compounds.
[0025] In some embodiments of the present application, the lithium source includes one or more combinations of lithium hydroxide, lithium oxide, lithium oxalate, lithium phosphate, lithium carbonate, lithium dihydrogen phosphate, and lithium hydrogen phosphate.
[0026] In some embodiments of the present application, the phosphorus source includes one or more combinations of phosphoric acid, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and iron phosphate.
[0027] In some embodiments of the present application, the M source includes one or more combinations of Fe source, Mn source, Co source, and Ni source.
[0028] The molar ratio of the lithium source, M source, N source and phosphorus source satisfies Li:M:N:P=(0.9-1.1):(0.9-1):(0.001-0.08):1.
[0029] In some embodiments of the present application, the step of sintering the positive electrode material precursor under an inert atmosphere includes: reacting at 100-200°C for 0.5-1h, then heating to 300-400°C, reacting for 1-2h, and continuing to heat to 600-800°C, reacting for 4-8h, wherein the heating rate in each stage is 2-5°C / min.
[0030] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes the battery positive electrode material according to the embodiment of the first aspect of the present application or the battery positive electrode material obtained by the preparation method according to the embodiment of the second aspect of the present application.
[0031] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, which includes the positive electrode sheet according to the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0033] Figure 1 This is an SEM image of the battery positive electrode material prepared in Example 5 of the present application.
[0034] Figure 2 This is the X-ray diffraction pattern of the battery positive electrode material prepared in Example 5 of the present application.
[0035] Figure 3 This is a TEM image of the battery positive electrode material coating layer prepared in Example 5 of the present application.
[0036] Figure 4 This is a charge and discharge curve diagram of the battery positive electrode material prepared in Example 5 of the present application when applied to a button battery. DETAILED DESCRIPTION
[0037] The features and exemplary embodiments of various aspects of the present application will be described in detail below. In the detailed description below, many specific details are set forth in order to provide a comprehensive understanding of the present application. However, it will be apparent to those skilled in the art that the present application can be implemented without some of these specific details. The following description of the embodiments is merely intended to provide a better understanding of the present application by illustrating examples of the present application. In the accompanying drawings and the following description, at least some of the well-known structures and technologies are not shown in order to avoid unnecessary ambiguity in the present application; and, for clarity, the sizes of some structures may be exaggerated. In addition, the features, structures, or characteristics described below may be combined in any suitable manner in one or more embodiments.
[0038] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish an entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In the description of the present application, it should be noted that, unless otherwise stated, the meaning of "plurality" is more than two. Moreover, the term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment comprising a series of elements not only include those elements, but also include other elements not clearly listed, or also include elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements limited by the statement "comprises..." do not exclude the presence of other identical elements in the process, method, article or equipment comprising the elements.
[0039] In order to solve the problems of the prior art, the embodiments of the present application provide a battery positive electrode material and a preparation method thereof, a positive electrode plate, and a lithium-ion battery, aiming to improve the conductivity of the battery positive electrode material and thereby improve its rate performance when used in secondary batteries.
[0040] Battery cathode materials
[0041] The first aspect of the present application provides a battery positive electrode material, comprising a phosphate-based active material core and a coating layer coating the phosphate-based active material core, the coating layer comprising a heteroatom-doped carbon material, the heteroatom comprising at least one of Group IIIA elements, and the heteroatom content in the heteroatom-doped carbon material being 1 wt% to 5 wt%.
[0042] In the context of this application, Group IIIA elements include elements such as boron, aluminum, gallium, indium, and thallium, and the atoms of these elements have three valence electrons. According to an embodiment of the present application, in the process of doping carbon materials, heteroatoms with three valence electrons replace the position of carbon atoms. When the three valence electrons of the heteroatoms form covalent bonds with carbon atoms, due to the lack of electrons, holes are generated in the crystal structure of the carbon material, which increases the concentration of hole carriers in the carbon material, thereby improving the conductivity of the carbon material. When the carbon material doped with heteroatoms is made into a coating layer of a battery positive electrode material, the conductivity of the positive electrode material can be improved, thereby improving the rate performance of the battery positive electrode material when applied to lithium-ion batteries.
[0043] According to the embodiments of the present application, the heteroatom content in the heteroatom-doped carbon material is limited to 1wt% to 5wt%. When the heteroatom content is lower than this range, the heteroatom elements doped in the carbon layer structure are relatively small, the hole carrier concentration provided is low, and the improvement in conductivity is not obvious; when the heteroatom content is higher than this range, the doping amount of heteroatoms is too high, and it is easy to form a heterophase, which may reduce the proportion of active substances on the one hand, and on the other hand, since the heterophase formed is a heteroatom compound, the overall conductivity is reduced, which affects the conductivity of the carbon layer.
[0044] In some embodiments, the heteroatom comprises one or more combinations of B, Al, and Ga.
[0045] In some embodiments, the coating layer has a thickness of 2 to 5 nm.
[0046] In some embodiments, the mass ratio of graphitized carbon to amorphous carbon in the heteroatom-doped carbon material is (0.6-2):1.
[0047] According to the embodiments of the present application, by adjusting the preparation process of the heteroatom-doped carbon material, the mass ratio of graphitized carbon and amorphous carbon in the heteroatom-doped carbon material is controlled within the above-mentioned range. The graphitized carbon has the characteristics of good conductivity, strong high-temperature stability and few side reactions, and the amorphous carbon has the characteristics of good coating effect, many pores, good wettability and being conducive to lithium ion transmission. By controlling the mass ratio of graphitized carbon and amorphous carbon within the above-mentioned range, the carbon layer coating effect can be further improved, and at the same time, the balance between electron transmission and ion diffusion can be adjusted, thereby reducing product polarization and improving electrochemical performance.
[0048] In some embodiments, the phosphate-based active material core comprises a chemical formula of Li x M y N z An active material for PO4, wherein M is selected from at least one element of Fe, Mn, Co, and Ni, N is selected from at least one element of V, Al, Ti, Ni, Nb, Mg, and Zr, 0.9≤x≤1.1, 0.9≤y≤1, and 0.001≤z≤0.08.
[0049] According to the embodiments of the present application, by using any one or more elements of V, Al, Ti, Ni, Nb, Mg, and Zr to bulk-dope the active material, the lattice structure of the positive electrode material is changed by metal bulk doping, which can broaden the lithium ion transmission channel, improve the continuity and stability of the lithium ion transmission channel, and reduce the diffusion energy barrier of lithium ions in the lattice, thereby accelerating the transmission speed of lithium ions and improving the conductivity of the positive electrode material. In addition, bulk doping can introduce new elements into the crystal structure of the positive electrode material. These doped elements can further stabilize the crystal structure of the positive electrode material and reduce the structural changes of the positive electrode material during the lithium ion insertion / deinsertion process, thereby improving the conductivity and cycle stability of the positive electrode material.
[0050] In some embodiments, the carbon content of the positive electrode material is 0.5 wt % to 2 wt %.
[0051] According to the embodiments of the present application, the addition of carbon can improve the conductivity of the positive electrode material and increase the battery's capacity. Excessively high or low carbon content will affect the performance of the positive electrode material. Specifically, when the carbon content of the positive electrode material is less than 0.5%, the material's conductivity is poor and the battery's internal resistance increases. When the carbon content of the positive electrode material exceeds 2%, the proportion of active material in the positive electrode material decreases, resulting in a decrease in the specific capacity of the positive electrode material and, consequently, a decrease in the battery's energy density. The carbon content of the positive electrode material can be selected to be 1% to 2%.
[0052] In some embodiments, the average particle size Dv50 of the positive electrode material is 0.5-1.5 μm.
[0053] The average particle size Dv50 has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. It can be measured using methods and instruments well-known in the art. For example, it can be measured using a laser diffractometer in accordance with GB / T 19077-2016 "Particle Size Analysis - Laser Diffraction Method".
[0054] In some embodiments, the specific surface area of the positive electrode material is 8 to 30 m 2 / g.
[0055] The specific surface area can be measured using methods and instruments known in the art. For example, it can be measured using the methods and instruments specified in GB / T 19587-2017 "Determination of the Specific Surface Area of Solid Substances by Gas Adsorption BET Method".
[0056] Preparation method of battery positive electrode material
[0057] An embodiment of the second aspect of the present application provides a method for preparing a positive electrode material for a battery, the method comprising the following steps S10 to S30:
[0058] S10, providing a phosphate-based active material and a heteroatom-doped carbon material respectively;
[0059] S20, mixing the heteroatom-doped carbon material and the phosphate-based active material and performing ball milling to obtain a positive electrode material precursor;
[0060] S30, sintering the cathode material precursor under an inert atmosphere to obtain a battery cathode material.
[0061] In some embodiments, the mass percentage of the heteroatom-doped carbon material relative to the phosphate-based active material is 0.5% to 2%.
[0062] According to the embodiments of the present application, by controlling the ratio of heteroatom-doped carbon material to phosphate-based active material within the above range, the prepared positive electrode material can have good conductivity and facilitate the diffusion of lithium ions. However, if the proportion of heteroatom-doped carbon material is too low, the positive electrode material will have poor conductivity and incomplete coating, which is prone to side reactions. If the proportion of heteroatom-doped carbon material is too high, the coating layer will be too thick, hindering the diffusion of lithium ions, and the proportion of active material will decrease, resulting in a decrease in the capacity of the positive electrode material.
[0063] In some embodiments, providing the heteroatom-doped carbon material includes: calcining a carbon source and a heteroatom source to obtain the heteroatom-doped carbon material.
[0064] According to an embodiment of the present application, the heteroatom source and the carbon source are mixed and then calcined to allow the heteroatoms to be doped into the carbon material structure.
[0065] In some embodiments, providing the heteroatom-doped carbon material includes: grinding a carbon source and a heteroatom source, and then calcining the ground carbon source to obtain the heteroatom-doped carbon material.
[0066] According to the embodiments of the present application, sufficient grinding before sintering can reduce the particle size of the carbon source and the heteroatom source, so that the heteroatoms can be better doped during the calcination process, resulting in a heteroatom-doped carbon material with a more stable structure.
[0067] In some embodiments, the calcination temperature is 600-1000°C, and optionally 800-1000°C.
[0068] In some embodiments, the calcination treatment time is 4 to 10 hours, optionally 6 to 10 hours, and further optionally 8 to 10 hours.
[0069] In some embodiments, the heteroatom source includes one or more compounds containing Group IIIA elements.
[0070] In some embodiments, the heteroatom source can be one or more of a boron-containing compound, an aluminum-containing compound, a gallium-containing compound, an indium-containing compound, and a thallium-containing compound.
[0071] Optionally, the boron-containing compound can be selected from one or more combinations of boric acid, borates, boron oxide, ammonium borate, and aluminum borate.
[0072] The aluminum-containing compound can be selected from one or more combinations of aluminum hydroxide, aluminum acetate, aluminum tribromide, aluminum phosphate or aluminum dihydrogen phosphate.
[0073] The gallium-containing compound may be selected from one or more combinations of gallium hydroxide, gallium oxide, gallium nitrate, gallium chloride and gallium nitride.
[0074] The indium-containing compound may be selected from one or more combinations of indium hydroxide, indium oxide, indium nitrate, indium chloride and indium phosphide.
[0075] The thallium-containing compound can be selected from one or more combinations of thallium hydroxide, thallium oxide, thallium nitrate, thallium chloride and thallium phosphide.
[0076] In some embodiments, the carbon source comprises one or more combinations of glucose, sucrose, and starch.
[0077] In some embodiments, providing the active material core includes: reacting a lithium source, a phosphorus source, an M source, and a N source, and separating a solid after the reaction to obtain the active material core.
[0078] In some embodiments, providing the active material core includes: reacting a lithium source and a phosphorus source, then adding an M source and a N source for a hydrothermal reaction, separating the solid after the reaction, washing, and drying to obtain the active material core.
[0079] In some embodiments, the temperature of the hydrothermal reaction is 160-200° C., for example, 170° C., 180° C., 190° C., or a range consisting of any two of the above values.
[0080] In some embodiments, the hydrothermal reaction time is 6 to 12 hours, for example, 8 hours, 9 hours, 10 hours, or 11 hours.
[0081] In some embodiments, the N source includes one or more of a vanadium-containing compound, an aluminum-containing compound, a titanium-containing compound, a nickel-containing compound, a niobium-containing compound, a magnesium-containing compound, and a zirconium-containing compound.
[0082] Optionally, the vanadium-containing compound includes one or a combination of ammonium metavanadate, vanadium pentoxide, and vanadyl oxalate.
[0083] Optionally, the aluminum-containing compound includes one or a combination of aluminum nitrate, aluminum acetate, and aluminum sulfate.
[0084] Optionally, the titanium-containing compound includes one of tetraethyl titanate, butyl titanate, ammonium hexafluorotitanate, or a combination thereof.
[0085] Optionally, the nickel-containing compound includes one of nickel acetate, nickel benzoate, nickel citrate, or a combination thereof.
[0086] Optionally, the niobium-containing compound includes one or more combinations of niobium sulfate, niobium oxalate, and niobium nitrate.
[0087] Optionally, the magnesium-containing compound includes one or more combinations of magnesium bicarbonate, magnesium nitrate, and magnesium sulfate.
[0088] Optionally, the zirconium-containing compound includes one or more combinations of zirconium acetate, zirconium citrate, and zirconium nitrate.
[0089] In some embodiments, the lithium source includes one or more combinations of lithium hydroxide, lithium oxide, lithium oxalate, lithium phosphate, lithium carbonate, lithium dihydrogen phosphate, and lithium hydrogen phosphate.
[0090] In some embodiments, the phosphorus source includes one or more combinations of phosphoric acid, ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and iron phosphate.
[0091] In some embodiments, the M source includes one or more combinations of a Fe source, a Mn source, a Co source, and a Ni source.
[0092] Optionally, the Fe source includes one or more combinations of ferrous sulfate, ferrous phosphate, ferrous oxalate, and ferrous pyrophosphate.
[0093] Optionally, the Mn source includes one or more combinations of manganese sulfate, manganese nitrate, manganese carbonate, manganese oxalate, manganese acetate, and manganese chloride.
[0094] Optionally, the Co source includes one or more combinations of cobalt sulfate, cobalt nitrate, cobalt carbonate, cobalt acetate, and cobalt chloride.
[0095] Optionally, the Ni source includes one or more combinations of nickel carbonate, nickel sulfate, and nickel nitrate.
[0096] In some embodiments, the molar ratio of the lithium source, the M source, the N source, and the phosphorus source satisfies Li:M:N:P=(0.9-1.1):(0.9-1):(0.001-0.08):1.
[0097] According to the embodiments of the present application, the molar ratio of lithium, M, N and phosphorus is controlled within the above range, which is conducive to the preparation of a positive electrode active material containing lithium, phosphorus, M and N elements in a suitable proportion, so that the prepared battery positive electrode material has good conductivity, and further has higher cycle performance and rate performance.
[0098] In some embodiments, the mass percentage of the heteroatom source relative to the carbon source is 1% to 5%.
[0099] According to the embodiments of the present application, by controlling the molar ratio of the carbon source and the heteroatom source within the above range, the heteroatoms can be effectively doped into the carbon material, thereby improving the conductivity of the carbon material. At the same time, the occurrence of impurity phases can be avoided, and the damage to the structure of the carbon material can be avoided.
[0100] In some embodiments, during the ball milling process, the ball mill rotates at a speed of 300-500 rpm.
[0101] In some embodiments, the ball milling treatment time is 4 to 8 hours.
[0102] In some embodiments, the ball milling treatment is followed by drying, the drying temperature is 80-100° C., and the drying time is 4-6 hours.
[0103] In some embodiments, the step of sintering the positive electrode material precursor under an inert atmosphere includes: reacting at 100-200°C for 0.5-1h, then heating to 300-400°C, reacting for 1-2h, and continuing to heat to 600-800°C, reacting for 4-8h, wherein the heating rate in each stage is 2-5°C / min.
[0104] According to the embodiment of the present application, the cathode material precursor adopts three-stage sintering. The first stage is sintered at 100-200 ° C to remove the crystal water in the cathode material precursor; the second stage is sintered at 300-400 ° C to remove the remaining volatiles, and finally the temperature is raised to 600-800 ° C for sintering. At this temperature, the degree of graphitization of the carbon layer is increased, and the residual organic functional groups are removed, while promoting crystal growth and improving the crystallinity of the particles. By adjusting the sintering temperature and time, the ratio of graphitized carbon and amorphous carbon in the carbon layer can be effectively controlled within a suitable range, thereby making the coating layer have a good coating effect while further improving the conductivity of the cathode material.
[0105] Positive electrode
[0106] An embodiment of the third aspect of the present application provides a positive electrode plate, which includes the battery positive electrode material according to the embodiment of the first aspect of the present application or the battery positive electrode material obtained by the preparation method according to the embodiment of the second aspect of the present application.
[0107] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material film layer, and the positive electrode material film layer includes a positive electrode active material, a conductive agent and a binder, wherein the positive electrode active material includes the battery positive electrode material provided according to the embodiment of the present application.
[0108] Examples of current collectors include aluminum foil, nickel mesh, or aluminum-plastic composite films. Examples of conductive agents include acetylene black, carbon black, graphite, or a combination thereof. Examples of binders include polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber latex, or a combination thereof.
[0109] lithium-ion batteries
[0110] An embodiment of the fourth aspect of the present application provides a lithium-ion battery, comprising a positive electrode sheet according to an embodiment of the third aspect of the present application.
[0111] In some embodiments, a lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.
[0112] As those skilled in the art will appreciate, the negative electrode sheet, separator, and electrolyte may be made of corresponding materials conventionally used in lithium-ion batteries, which will not be described in detail here.
[0113] Example
[0114] The present invention is described below with reference to specific examples. It should be noted that the examples described below are exemplary and are intended only to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used without manufacturer's indication are all commercially available conventional products.
[0115] Example 1
[0116] A battery positive electrode material is prepared by the following method:
[0117] Preparation of active material core
[0118] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0119] S20, add 55.6g of ferrous sulfate heptahydrate and 0.5769g of ammonium metavanadate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 160°C for 12h;
[0120] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a vanadium-doped active material core. The chemical formula of the active material core is LiFeV 0.03 PO4;
[0121] Preparation of heteroatom-doped carbon materials
[0122] S40, taking 1 g of anhydrous glucose and 0.0515 g of boron oxide, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 600° C. at a rate of 2° C. / min, keeping the temperature constant for 10 hours, and cooling them to room temperature to obtain a boron-doped carbon material;
[0123] Preparation of battery positive electrode materials
[0124] S50, mixing 0.2 g of boron-doped carbon material and 10 g of vanadium-doped active material core, adding ethanol and ball milling, the ball mill speed is 300 rpm, the ball milling time is 8 h, after the ball milling is completed, transferring the mixture to an 80° C. oven and drying for 6 h to remove ethanol, to obtain a carbon-containing precursor;
[0125] S60. Place the carbon-containing precursor in a tubular furnace and sinter it step by step under a nitrogen atmosphere. Raise the temperature from room temperature to 100°C at a rate of 2°C / min and keep it for 1 hour. Then raise the temperature to 300°C at a rate of 2°C / min and keep it for 2 hours. Continue to raise the temperature to 600°C at a rate of 2°C / min and keep it for 8 hours. After sintering, naturally cool it to room temperature to obtain the battery positive electrode material.
[0126] Example 2
[0127] A battery positive electrode material is prepared by the following method:
[0128] Preparation of active material core
[0129] S10, taking 25.176g of lithium phosphate, 55.6g of ferrous sulfate heptahydrate and 1.0649g of nickel acetate tetrahydrate, adding 30mL of ethylene glycol under magnetic stirring, stirring for 0.5h, and then transferring to a hydrothermal reactor, and carrying out a hydrothermal reaction at 180°C for 9h;
[0130] S20, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol, respectively, and then dried in an oven at 80°C to obtain a nickel-doped active material core. The chemical formula of the active material core is LiFeNi 0.02 PO4;
[0131] Preparation of heteroatom-doped carbon materials
[0132] S30, taking 1 g of anhydrous glucose and 0.0515 g of boron oxide, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 800° C. at a rate of 3° C. / min, maintaining the temperature for 7 h, and cooling them to room temperature to obtain a boron-doped carbon material;
[0133] Preparation of battery positive electrode materials
[0134] S40, mixing 0.2 g of boron-doped carbon material and 10 g of nickel-doped active material core, adding ethanol and ball milling, the ball mill speed is 400 rpm, the ball milling time is 6 h, after the ball milling is completed, transferring the mixture to an 80° C. oven and drying for 6 h to remove ethanol, to obtain a carbon-containing precursor;
[0135] S50. Place the carbon-containing precursor in a tubular furnace and sinter it step by step under a nitrogen atmosphere. Raise the temperature from room temperature to 150°C at a rate of 3°C / min and keep it for 1 hour. Then raise the temperature to 350°C at a rate of 3°C / min and keep it for 1.5 hours. Continue to raise the temperature to 700°C at a rate of 3°C / min and keep it for 6 hours. After sintering, naturally cool it to room temperature to obtain the battery positive electrode material.
[0136] Example 3
[0137] A battery positive electrode material is prepared by the following method:
[0138] Preparation of active material core
[0139] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0140] S20, add 55.6g of ferrous sulfate heptahydrate and 3.4927g of aluminum nitrate nonahydrate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 200°C for 6h;
[0141] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain an aluminum-doped active material core. The chemical formula of the active material core is LiFeAl 0.04 PO4;
[0142] Preparation of heteroatom-doped carbon materials
[0143] S40, taking 1 g of anhydrous sucrose and 0.0515 g of boric acid, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 1000° C. at a rate of 5° C. / min, maintaining the temperature for 4 h, and cooling them to room temperature to obtain a boron-doped carbon material;
[0144] Preparation of battery positive electrode materials
[0145] S50, mixing 0.2 g of boron-doped carbon material and 10 g of aluminum-doped active material core, adding ethanol and ball milling, the ball mill speed is 500 rpm, the ball milling time is 4 h, after the ball milling is completed, transferring the mixture to an 80° C. oven and drying for 6 h to remove ethanol, to obtain a carbon-containing precursor;
[0146] S60. Place the carbon-containing precursor in a tubular furnace and sinter it step by step under a nitrogen atmosphere. Raise the temperature from room temperature to 200°C at a rate of 5°C / min and keep it for 0.5h. Then raise the temperature to 400°C at a rate of 5°C / min and keep it for 2h. Continue to raise the temperature to 800°C at a rate of 5°C / min and keep it for 4h. After sintering, naturally cool it to room temperature to obtain the battery positive electrode material.
[0147] Example 4
[0148] A battery positive electrode material is prepared by the following method:
[0149] Preparation of active material core
[0150] S10, dissolving 27.022 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 90 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0151] S20, add 22.24g of ferrous sulfate heptahydrate, 18.12g of manganese sulfate monohydrate and 1.1971g of tetraethyl titanate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 180°C for 8h;
[0152] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a titanium-doped active material core. The chemical formula of the active material core is LiMn 0.6 Fe 0.4 Ti 0.02 PO4;
[0153] Preparation of heteroatom-doped carbon materials
[0154] S40, taking 1 g of anhydrous starch and 0.0515 g of ammonium borate, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 800° C. at a rate of 4° C. / min, maintaining the temperature for 8 h, and cooling them to room temperature to obtain a boron-doped carbon material;
[0155] Preparation of battery positive electrode materials
[0156] S50, mixing 0.2 g of boron-doped carbon material and 10 g of titanium-doped active material core, adding ethanol and ball-milling, the ball mill speed is 480 rpm, the ball milling time is 4 h, and after the ball milling is completed, the mixture is transferred to an 80° C. oven and dried for 6 h to remove ethanol, thereby obtaining a carbon-containing precursor;
[0157] S60. Place the carbon-containing precursor in a tubular furnace and sinter it step by step under a nitrogen atmosphere. Raise the temperature from room temperature to 180°C at a rate of 5°C / min and keep it for 1 hour. Then raise the temperature to 400°C at a rate of 4°C / min and keep it for 2 hours. Continue to raise the temperature to 800°C at a rate of 2°C / min and keep it for 4 hours. After sintering, naturally cool it to room temperature to obtain the battery positive electrode material.
[0158] Example 5
[0159] A battery positive electrode material is prepared by the following method:
[0160] Preparation of active material core
[0161] S10, dissolving 28.952 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 150 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0162] S20, add 22.24g of ferrous sulfate heptahydrate, 18.12g of manganese sulfate monohydrate and 0.5769g of ammonium metavanadate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 180°C for 8h;
[0163] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a vanadium-doped active material core. The chemical formula of the active material core is LiMn 0.6 Fe 0.4 V 0.03 PO4;
[0164] Preparation of heteroatom-doped carbon materials
[0165] S40, taking 1 g of anhydrous glucose and 0.04 g of gallium nitrate, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 750° C. at a rate of 2° C. / min, maintaining the temperature for 6 h, and cooling them to room temperature to obtain a gallium-doped carbon material;
[0166] Preparation of battery positive electrode materials
[0167] S50, mixing 0.2 g of gallium-doped carbon material and 10 g of vanadium-doped active material core, adding ethanol and ball milling, the ball mill speed is 480 rpm, the ball milling time is 4 h, and after the ball milling is completed, the mixture is transferred to an 80° C. oven and dried for 6 h to remove ethanol, thereby obtaining a carbon-containing precursor;
[0168] S60. Place the carbon-containing precursor in a tubular furnace and sinter it step by step under a nitrogen atmosphere. Raise the temperature from room temperature to 180°C at a rate of 5°C / min and keep it for 1 hour. Then raise the temperature to 350°C at a rate of 2°C / min and keep it for 2 hours. Continue to raise the temperature to 600°C at a rate of 2°C / min and keep it for 4 hours. After sintering, naturally cool it to room temperature to obtain the battery positive electrode material.
[0169] Example 6
[0170] A battery positive electrode material is prepared by the following method:
[0171] Preparation of active material core
[0172] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0173] S20, add 22.24g of ferrous sulfate heptahydrate, 18.12g of manganese sulfate monohydrate and 0.5769g of ammonium metavanadate to the Li3PO4 suspension, stir for 0.5h and then transfer to a hydrothermal reactor for a hydrothermal reaction at 180°C for 8h;
[0174] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a vanadium-doped active material core. The chemical formula of the active material core is LiMn 0.6 Fe 0.4 V 0.03 PO4;
[0175] Preparation of heteroatom-doped carbon materials
[0176] S40, taking 1 g of anhydrous glucose and 0.0515 g of boron oxide, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 750° C. at a rate of 2° C. / min, maintaining the temperature for 6 h, and cooling them to room temperature to obtain a boron-doped carbon material;
[0177] Preparation of battery positive electrode materials
[0178] S50, mixing 0.2 g of boron-doped carbon material and 10 g of vanadium-doped active material core, adding ethanol and ball milling, the ball mill speed is 480 rpm, the ball milling time is 4 h, and after the ball milling is completed, the mixture is transferred to an 80° C. oven and dried for 6 h to remove ethanol, thereby obtaining a carbon-containing precursor;
[0179] S60. Place the carbon-containing precursor in a tubular furnace and sinter it step by step under a nitrogen atmosphere. Raise the temperature from room temperature to 180°C at a rate of 5°C / min and keep it for 1 hour. Then raise the temperature to 350°C at a rate of 2°C / min and keep it for 2 hours. Continue to raise the temperature to 600°C at a rate of 2°C / min and keep it for 4 hours. After sintering, naturally cool it to room temperature to obtain the battery positive electrode material.
[0180] Example 7
[0181] A battery positive electrode material is prepared by the following method:
[0182] Preparation of active material core
[0183] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0184] S20, add 55.6g of ferrous sulfate heptahydrate and 0.5769g of ammonium metavanadate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 180°C for 8h;
[0185] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a vanadium-doped active material core. The chemical formula of the active material core is LiFeV 0.03 PO4;
[0186] Preparation of heteroatom-doped carbon materials
[0187] S40, taking 1 g of anhydrous glucose and 0.0515 g of boron oxide, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 750° C. at a rate of 2° C. / min, maintaining the temperature for 6 h, and cooling them to room temperature to obtain a boron-doped carbon material;
[0188] Preparation of battery positive electrode materials
[0189] S50, mixing 0.2 g of boron-doped carbon material and 10 g of vanadium-doped active material core, adding ethanol and ball milling, the ball mill speed is 480 rpm, the ball milling time is 4 h, and after the ball milling is completed, the mixture is transferred to an 80° C. oven and dried for 6 h to remove ethanol, thereby obtaining a carbon-containing precursor;
[0190] S60, placing the carbon-containing precursor in a tubular furnace and sintering it under a nitrogen atmosphere at a sintering temperature of 600° C. for 7 hours. After sintering, naturally cooling it to room temperature to obtain a battery positive electrode material.
[0191] Example 8
[0192] The only difference between Example 8 and Example 1 is: S60, placing the carbon-containing precursor in a tubular furnace and performing two-stage sintering under a nitrogen atmosphere, heating to 300°C at a rate of 2°C / min and keeping warm for 2 hours, continuing to heat to 600°C at a rate of 2°C / min and keeping warm for 8 hours, and naturally cooling to room temperature after sintering to obtain a battery positive electrode material.
[0193] Comparative Example 1
[0194] A battery positive electrode material is prepared by the following method:
[0195] Preparation of active material core
[0196] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0197] S20, add 55.6g of ferrous sulfate heptahydrate and 0.5769g of ammonium metavanadate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 160°C for 12h;
[0198] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a vanadium-doped active material core. The chemical formula of the active material core is LiFeV 0.03 PO4;
[0199] Preparation of battery positive electrode materials
[0200] S40, mixing 1 g of anhydrous glucose and 10 g of vanadium-doped active material core, adding ethanol and ball milling, the ball mill speed is 300 rpm, the ball milling time is 8 h, after the ball milling is completed, transferring the mixture to an 80° C. oven and drying for 6 h to remove ethanol, to obtain a carbon-containing precursor;
[0201] S50. Place the carbon-containing precursor in a tubular furnace and perform step-by-step sintering under a nitrogen atmosphere. Raise the temperature from room temperature to 100°C at a rate of 2°C / min and keep it for 1 hour. Then raise the temperature to 300°C at a rate of 2°C / min and keep it for 2 hours. Continue to raise the temperature to 600°C at a rate of 2°C / min and keep it for 8 hours. After sintering, naturally cool to room temperature to obtain the battery positive electrode material.
[0202] Comparative Example 2
[0203] A battery positive electrode material is prepared by the following method:
[0204] Preparation of active material core
[0205] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0206] S20, add 55.6g of ferrous sulfate heptahydrate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 160°C for 12h;
[0207] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol, respectively, and then dried in an oven at 80° C. to obtain a positive electrode active material core, the chemical formula of which is LiFePO4;
[0208] Preparation of heteroatom-doped carbon materials
[0209] S40, taking 1 g of anhydrous glucose and 0.0515 g of boron oxide, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 600° C. at a rate of 2° C. / min, keeping the temperature constant for 10 hours, and cooling them to room temperature to obtain a boron-doped carbon material;
[0210] Preparation of battery positive electrode materials
[0211] S50, mixing 0.2 g of boron-doped carbon material and 10 g of cathode material core, adding ethanol and ball milling, the ball mill speed is 300 rpm, the ball milling time is 8 h, after the ball milling is completed, transferring the mixture to an 80° C. oven and drying for 6 h to remove ethanol, thereby obtaining a carbon-containing precursor;
[0212] S60. Place the carbon-containing precursor in a tubular furnace and sinter it step by step under a nitrogen atmosphere. Raise the temperature from room temperature to 100°C at a rate of 2°C / min and keep it for 1 hour. Then raise the temperature to 300°C at a rate of 2°C / min and keep it for 2 hours. Continue to raise the temperature to 600°C at a rate of 2°C / min and keep it for 8 hours. After sintering, naturally cool it to room temperature to obtain the battery positive electrode material.
[0213] Comparative Example 3
[0214] A battery positive electrode material is prepared by the following method:
[0215] Preparation of active material core
[0216] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0217] S20, add 55.6g of ferrous sulfate heptahydrate and 0.5769g of ammonium metavanadate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 160°C for 12h;
[0218] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a vanadium-doped active material core. The chemical formula of the active material core is LiFeV 0.03 PO4;
[0219] Preparation of heteroatom-doped carbon materials
[0220] S40, taking 1 g of anhydrous glucose and 0.0772 g of boron oxide, adding them to an agate mortar and grinding them thoroughly, placing them in a tube furnace under an argon atmosphere for sintering, heating them from room temperature to 600° C. at a rate of 2° C. / min, keeping the temperature constant for 10 h, and cooling them to room temperature to obtain a boron-doped carbon material;
[0221] Preparation of battery positive electrode materials
[0222] S40, mixing 0.2 g of boron-doped carbon material and 10 g of vanadium-doped active material core, adding ethanol and ball milling, the ball mill speed is 300 rpm, the ball milling time is 8 h, after the ball milling is completed, transferring the mixture to an 80° C. oven and drying for 6 h to remove ethanol, to obtain a carbon-containing precursor;
[0223] S50. Place the carbon-containing precursor in a tubular furnace and perform step-by-step sintering under a nitrogen atmosphere. Raise the temperature from room temperature to 160°C at a rate of 2°C / min and keep it for 1 hour. Then raise the temperature to 300°C at a rate of 2°C / min and keep it for 2 hours. Continue to raise the temperature to 600°C at a rate of 2°C / min and keep it for 8 hours. After sintering, naturally cool to room temperature to obtain the battery positive electrode material.
[0224] Comparative Example 4
[0225] A battery positive electrode material is prepared by the following method:
[0226] Preparation of active material core
[0227] S10, dissolving 25.176 g of lithium hydroxide monohydrate in 150 mL of deionized water, then adding 30 mL of ethylene glycol and 23.05 g of phosphoric acid dropwise under magnetic stirring to obtain a Li3PO4 suspension;
[0228] S20, add 55.6g of ferrous sulfate heptahydrate and 0.5769g of ammonium metavanadate to the Li3PO4 suspension, stir for 0.5h, then transfer to a hydrothermal reactor and carry out a hydrothermal reaction at 160°C for 12h;
[0229] S30, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the precipitate is separated, washed with deionized water and ethanol respectively, and then dried in an oven at 80°C to obtain a vanadium-doped active material core. The chemical formula of the active material core is LiFeV 0.03 PO4;
[0230] Preparation of battery positive electrode materials
[0231] S50, mixing 10 g of vanadium-doped active material cores, adding ethanol and ball milling, the ball mill speed is 300 rpm, the ball milling time is 8 h, and after the ball milling is completed, the mixture is transferred to an 80° C. oven and dried for 6 h to remove the ethanol, to obtain a precursor;
[0232] S60. Place the precursor in a tubular furnace and perform step-by-step sintering under a nitrogen atmosphere. Raise the temperature from room temperature to 100°C at a rate of 2°C / min and keep it for 1 hour. Then raise the temperature to 300°C at a rate of 2°C / min and keep it for 2 hours. Continue to raise the temperature to 600°C at a rate of 2°C / min and keep it for 8 hours. After sintering, naturally cool to room temperature to obtain the battery positive electrode material.
[0233] Test section
[0234] 1. The battery cathode material was tested by scanning electron microscopy, X-ray diffraction and transmission electron microscopy respectively. The test results are as follows: Figure 1-3 shown.
[0235] in, Figure 1 The SEM image of the battery positive electrode material prepared in this embodiment is shown. Figure 1 It can be seen that the positive electrode material has a high degree of dispersion and the particles are round and have a high sphericity. Figure 2 The X-ray diffraction pattern of the battery positive electrode material is shown in FIG. , from which it can be seen that the positive electrode material has no impurity phase and has a high degree of crystallinity. Figure 3 The TEM image of the positive electrode material is shown, and it can be seen that the coating layer is regular and uniform.
[0236] 2. Average particle size of battery positive electrode material Dv50
[0237] The battery positive electrode materials prepared in the examples and comparative examples were measured using a laser particle size analyzer in accordance with GB / T 19077-2016. The test results are shown in Table 1.
[0238] 3. Specific surface area of battery positive electrode material
[0239] 5g of the resulting battery cathode material powder was placed in a sample tube and heated to degas. After degassing, the sample was weighed and placed on a testing instrument. At a constant low temperature (-296.7°C), the amount of gas adsorbed on the solid surface at different relative pressures was measured. Based on the Brownauer-Etter-Teller (BET) multilayer adsorption theory and its formula, the sample monolayer adsorption capacity was calculated, and the specific surface area of the cathode material was calculated. The test results are shown in Table 1.
[0240] Table 1
[0241] Dv50(μm) <![CDATA[Specific surface area (m 2 / g)]]> Coating thickness (nm) Example 1 1.37 10.84 3 Example 2 1.35 11.66 3 Example 3 1.20 12.31 3 Example 4 0.55 17.66 4 Example 5 0.65 16.50 4 Example 6 0.70 15.20 4 Example 7 1.29 11.50 3 Example 8 1.23 11.56 3 Comparative Example 1 1.40 10.02 3 Comparative Example 2 1.55 12.54 3 Comparative Example 3 1.38 11.36 3 Comparative Example 4 1.66 9.63 /
[0242] 4. Preparation of lithium-ion batteries
[0243] Preparation of positive electrode sheets: The battery positive electrode materials prepared in each embodiment and comparative example were respectively used as positive electrode active materials, conductive carbon black was used as a conductive agent, and polyvinylidene fluoride was used as a binder. The positive electrode active material, the conductive agent, and polyvinylidene fluoride were mixed in a mass ratio of 93.74:2.33:4.2, and then dissolved in an appropriate amount of N-methylpyrrolidone solvent. The mixture was ground into a slurry and then coated on an aluminum foil. The mixture was dried at 120°C for 12 hours to prepare a positive electrode sheet.
[0244] Preparation of button batteries: lithium sheet as negative electrode, polypropylene microporous membrane as separator, 1 mol / L LiF6PO4 electrolyte, ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate with a volume ratio of 1:1:1, and button batteries with model CR2032 were assembled in a glove box.
[0245] The button cells were subjected to charge and discharge tests with a test voltage range of 2 to 3.75 V and a charge current of 0.1 C and 1 C. The charge and discharge test results are shown in Table 2 below.
[0246] Table 2
[0247]
[0248] Combined with the data in Table 2, it can be seen that the use of heteroatom-doped carbon materials as carbon coatings, combined with metal-doped positive electrode active materials, can further enhance the conductivity of battery positive electrode materials. Comparing the charge and discharge data of the examples and comparative examples, it can be seen that the doped battery positive electrode materials have good charge and discharge capacities at both 0.1C and 1C rates. By adjusting the parameters and preparation process of the battery positive electrode materials, the resulting positive electrode materials can be applied to button cells, achieving charge and discharge capacities exceeding 160 mAh / g at both 0.1C and 1C rates, demonstrating excellent performance.
[0249] Specifically, in combination with Example 1 and Comparative Example 1 and their experimental data, in Example 1, heteroatoms were used to dope the carbon material, and the corresponding button battery test process had a significant improvement in the first charge and discharge specific capacities of 0.1C and 1C. This may be because the doping of heteroatoms effectively increased the hole carrier concentration in the carbon material, thereby increasing the conductivity of the carbon layer, reducing the polarization internal resistance of the battery, and improving the electrochemical performance of the battery.
[0250] Combined with Example 1 and Comparative Example 2 and their experimental data, in Example 1, metal elements were used to dope the active material, and a phosphate material with cation defects was synthesized by metal cation doping. In the process of high-valent dopant atoms replacing the original atoms, due to the valence balance of the compound, some Li, Fe / Mn defects and a certain amount of Fe appeared in the phosphate lattice. 2+ / Fe 3+ This is beneficial to the diffusion of Li ions and electrons in the solid phase, thereby improving the electrochemical performance of the crystal. When the positive electrode material is used in a secondary battery, it exhibits a higher first charge and discharge specific capacity.
[0251] Compared with Example 1, Comparative Example 3 increases the doping amount of heteroatoms in the heteroatom-doped carbon material. The test results show that the initial charge and discharge specific capacity is greatly reduced. This indicates that when the heteroatom doping amount is higher than the range specified in this application, the heteroatom doping amount is too high and it is easy to form a heterophase. On the one hand, it may reduce the proportion of active substances. On the other hand, since the heterophase formed is a boron atom compound, the overall conductivity is reduced, which affects the conductivity of the carbon layer.
[0252] Examples 7 and 8 further adjusted the sintering process of the positive electrode material precursor. By comparing with the experimental data of Example 1, it was found that the initial charge and discharge specific capacity of the battery was reduced to a certain extent. This may be because the volatile matter and moisture in the positive electrode material were not completely removed. During the calcination process, these volatile matter and moisture accumulated inside the powder, resulting in uneven heating overall, and the particles were easy to stick together. The formed particles contained more grain boundaries, which was not conducive to the diffusion of lithium ions, thereby affecting the electrochemical properties of the positive electrode material.
[0253] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A battery positive electrode material, characterized in that: include: A phosphate-based active material core and a coating layer coating the phosphate-based active material core, wherein the coating layer comprises a heteroatom-doped carbon material, wherein the heteroatom comprises at least one of the IIIA group elements, and the heteroatom content of the heteroatom-doped carbon material is 1 wt% to 5 wt%; The carbon content of the positive electrode material is 0.5wt% to 2wt%; The average particle size Dv50 of the positive electrode material is 0.5 to 1.5 μm.
2. The battery positive electrode material according to claim 1, characterized in that The heteroatoms include one or more combinations of B, Al, Ga, and / or The coating layer has a thickness of 2 to 5 nm, and / or The mass ratio of graphitized carbon to amorphous carbon in the heteroatom-doped carbon material is (0.6-2):
1.
3. The battery positive electrode material according to claim 1, characterized in that: The active material core includes a chemical formula of Li x M y N z An active material of PO4, wherein M is selected from at least one element of Fe, Mn, Co, and Ni, N is selected from at least one element of V, Al, Ti, Ni, Nb, Mg, and Zr, 0.9≤x≤1.1, 0.9≤y≤1, and 0.001≤z≤0.
08.
4. The battery positive electrode material according to claim 1, characterized in that The specific surface area of the positive electrode material is 8 to 30 m 2 / g.
5. The method for preparing the positive electrode material of a battery according to any one of claims 1 to 4, characterized in that: include: providing phosphate-based active materials and heteroatom-doped carbon materials respectively; The heteroatom-doped carbon material and the phosphate-based active material are mixed and subjected to ball milling treatment to obtain a positive electrode material precursor; The positive electrode material precursor is sintered in an inert atmosphere to obtain a positive electrode material for a battery.
6. The method for preparing a positive electrode material for a battery according to claim 5, characterized in that: The providing of the heteroatom-doped carbon material comprises: taking a carbon source and a heteroatom source and performing calcination treatment to obtain the heteroatom-doped carbon material, and / or The providing of the phosphate active material comprises: reacting a lithium source, a phosphorus source, an M source and a N source, separating a solid after the reaction to obtain the phosphate active material, and / or The mass percentage of the heteroatom-doped carbon material relative to the phosphate-based active material is 0.5% to 2%; in, The M source includes one or more combinations of Fe source, Mn source, Co source and Ni source. The N source includes one or more combinations of vanadium-containing compounds, aluminum-containing compounds, titanium-containing compounds, nickel-containing compounds, niobium-containing compounds, magnesium-containing compounds, and zirconium-containing compounds.
7. The method for preparing a positive electrode material for a battery according to claim 6, characterized in that: The heteroatom source includes one or more compounds containing Group IIIA elements, and / or The carbon source includes one or more combinations of glucose, sucrose, starch, and / or The mass percentage of the heteroatom source relative to the carbon source is 1% to 5%; and / or The molar ratio of the lithium source, M source, N source and phosphorus source satisfies Li:M:N:P=(0.9-1.1):(0.9-1):(0.001-0.08):
1.
8. The method for preparing a positive electrode material for a battery according to claim 5, characterized in that: The step of sintering the cathode material precursor under an inert atmosphere includes: reacting at 100-200°C for 0.5-1h, then heating to 300-400°C, reacting for 1-2h, and continuing to heat to 600-800°C, reacting for 4-8h, wherein the heating rate in each stage is 2-5°C / min.
9. A positive electrode sheet, characterized in that: The invention comprises the battery positive electrode material according to any one of claims 1 to 4 or the battery positive electrode material obtained by the preparation method according to any one of claims 5 to 8.
10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Boron-doped modified graphene material, preparation method and application
CN104299798A
Preparation method and application of metal-doped carbon in-situ coated lithium iron phosphate electrode material
CN114551823A
Modified phosphate positive electrode material and preparation method thereof, positive plate and secondary battery
CN116504967A
Cited By
Positive electrode material of battery and preparation method therefor, positive electrode sheet, and lithium-ion battery
EP4787465A1